Natural resource curse : The case of Russia - Belyakova, Elena; Frömmel, Tomáš; Máslo, Lukáš Augustin, 1985-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2017)
The purpose of this paper is to provide insight into the problem of the natural resource curse, particularly in the Russian Federation, with respect to history, changes in oil prices and the situation in the world arena. With the hypothesis that the changes in oil prices affect the Russian GDP and the development of other non-oil based industries, two different regressions for two time periods are run. The results of the regressions and subsequent test confirm the hypothesis that Russian GDP depends on the oil prices and on changes on the world resource market. It is found, that in the Soviet period there was no dependence of Soviet economy on oil export and prices. The results are in support of the previous paper, written by Benedictow et al. (2010), that indeed Russian economy suffers from the natural resource curse.
Vedoucí práce: Tomáš Frömmel
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses